Rancang Bangun Alat Pengukur Jarak Berbasis Arduino Uno dengan Sensor Ultrasonik - Arum, Adilla Safna; Kadavi, Fadhil Muhammad; Pratama, Yhoga Putra; Fitrianti, Friska Ayu (Journal of Mechanical Engineering and Applied Technology, 2024)
Instrument equipment is part of the equipment installed on the tool intended to find out and get the desired data from an activity. One of the important instrument equipment in various fields is the measuring instrument. A jaral measuring instrument is basically a tool to find out how much distance or how long the distance is from an object. The need for measuring instruments used and having high accuracy encourages the creation of more measuring instruments. The purpose of this study is the development of a prototype distance measuring instrument based on Arduino uno microcontroller using ultrasonic sensor HC-SR04. This ultrasonic sensor uses the speed of sound to measure the distance with a magnitude of 340 m/s, thus knowing the time between sending the signal and receiving the signal so that the distance between the transmitter and the receiving object can be calculated. The distance measurement data will then be displayed on a 16 x 2 liquid crystal display for easy reading. This design is controlled through the Arduino Uno R3 kit based on ATMEGA 328 P which is implemented in an acrylic plastic plate as a place for the circuit. The test results from the distance measurement instrument research have a measurement error value range of 0% - 0.067%, so it can be said that the distance measuring instrument from this study has a high accuracy value.